Masculinity and identity in Irish literature : heroes, lads, and fathers - Tully de Lope, Cassandra S. (New York, NY : Routledge, 2024)
"This book addresses Irish identity in Irish literature, especially masculinity in some of its forms through an interdisciplinary methodology. The study of language performance through literary analysis and corpus studies, will enable readers to approach literary texts from both quantitative and qualitative perspectives, to take advantage of the texts' full potential as well as examining these same texts through the perspective of gender identity. This will be carried out through a specialised corpus composed of eighteen novels written by twentieth and twenty-first-century male Irish authors. Thus, the language and behaviour patterns of contemporary Irish masculinity can be found as part of these male characters' performance of identity. This book is primarily aimed at undergraduate and graduate students who wish to either introduce themselves in the study of gender and identity in an Irish context as well as researchers looking for interdisciplinary methodologies of study. What is more, it can present researchers with varied options of analysis that corpus studies have not yet touched upon so thoroughly such as masculinity and Irish literature. As a monograph meant to show analysts new fields of study in Irish literature, this book will sell to academic libraries and can be used in MA courses"--
Keywords: English fiction -- Irish authors -- History and criticism; English fiction -- Male authors -- History and criticism; Masculinity in literature; Identity (Philosophical concept) in literature; Gender identity in literature; Group identity in literature; Men in literature; Ireland -- In literature; LITERARY CRITICISM / General; LITERARY CRITICISM / European / English, Irish, Scottish, Welsh